Answer:
x = 3
y = 3
Explanation:
To solve x - 3y = -6 and 2x - y = 3 using equal value method, express othe same variable from each equation.
1st equation:
![x=3y-6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zcy1uyc4usezcz1zbf7gx1l61jzidhvnx2.png)
2nd equation:
![2x=y+3\\ \\x=(1)/(2)(y+3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/plmexdnnv6u3np86ray8v6f7vv7vg2bj6t.png)
Equate the right sides of these expressions:
![3y-6=(1)/(2)(y+3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dho0h93rgsiv9zj9r2ikwhgtodcx4qk23p.png)
Multiply by 2:
![6y-12=y+3\\ \\6y-y=3+12\\ \\5y=15\\ \\y=(15)/(5)\\ \\y=3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pjwqz32s4qjifbfpkglkrrslunoab21ndk.png)
Substitute it into the first expression:
![x=3\cdot 3-6\\ \\x=9-6\\ \\x=3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/y7lj0h62ywr4yy6a11fnoxco8q7lcq2dab.png)